Large-scale preparation of micro-gradient structured sub-micro fibrous membranes with narrow diameter distributions for high-efficiency air purification. Issue 12 (21st October 2019) - Zhou, Mengjuan; Fang, Mengzhen; Quan, Zhenzhen; Zhang, Hongnan; Qin, Xiaohong; Wang, Rongwu; Yu, Jianyong
Abstract : Micro-gradient structured PAN sub-micro fibrous membrane with high-efficiency air purification performance was fabricated via one-step free surface electrospinning with large-scale yield, firstly demonstrated as air filters. Abstract : Herein, micro-gradient structured polyacrylonitrile (PAN) sub-micro fibrous membranes composed of coarse, medium, and fine (C, M, and F) fiber layers with different fiber diameters in the submicron scale range were fabricated via one-step free surface electrospinning with large-scale productivity and demonstrated for the first time as air filters, respectively. The sub-micro fibers with narrow diameter distributions of each layer were regulated precisely in the micro-gradient structure; moreover, the influence of the arrangement of the layers on the performance of the membranes was analyzed systematically, among which the F–M–C membrane displayed optimal performance (filtration efficiency of 99.28% and pressure drop of 55.86 Pa). Additionally, the filtration performance of the composite membranes could be further improved to an efficiency of 99.99% and a pressure drop of 92 Pa only by the surface modification of the finest fibrous layer. Furthermore, the micro-gradient structures of the membranes could be regulated and arbitrarily fabricated with different gradient degrees, even at the nanometer level. By polymer blending, the upgraded micro-gradient-structured filter (the average fiber diameters of each layer were only 200, 110 and 70 nm) possessed ∼1 μm average pore size, a large specific surface area (53.12 m 2 g −1 ) and an excellent efficiency of 99.97% (F–M–C) with a resistance of 106.8 Pa, superior to those of a homogeneous PAN filter. The results suggest that micro-gradient-structured fibrous membranes composed of C, M, and F layers with tortuous channels can efficiently separate different sized PMs from the airstream through capturing mechanisms. The cost-effective micro-gradient filter media produced by one-step free surface electrospinning is promising for industrial production and commercial applications.